BENTUK PENGACUAN DALAM WACANA MEDIA MASSA CETAK - Riyanto, Sugeng (Jurnal Penelitian Humaniora, 2015)
This study deals with referring expressions used in Indonesian newspapers: Kompas, Seputar Indonesia, Solopos, and Suara Merdeka. The aim of this research is to describe the kinds of referring expressions used in these newspapers. This is a qualitative research. The data were in the forms of referring expressions used in Kompas, Seputar Indonesia, Solopos, and Suara Merdeka. The data were analyzed qualitatively which includes description, classification, and explanation. The results indicate that there are several types of referring expressions used in these newspapers, namely: exophoric referring expressions and endophoric referring expressions. The endophoric referring expression consisted of anaphoric referring expression and cataphoric referring expressions.